The ever after [large type] : a novel - Pekkanen, Sarah (Center Point Large Print, 2018)
"An enthralling domestic drama that goes deep into a marriage in crisis, peeling back layers of secrets to discover where the relationship veered off course--and whether it is worth saving"--